Hubungan Guru dan Murid - Islamiyah, Thayyibatul; Faelasup, Faelasup (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2024)
The relationship between teachers and students plays a crucial role in modern education, influencing not only academic outcomes but also the social-emotional development of students. This study aims to explore the impact of the quality of teacher-student relationships on learning achievement, student motivation, and social interactions in schools. The research methodology involved a systematic review of relevant literature and analysis of relevant empirical studies. The findings indicate that a positive relationship between teachers and students significantly enhances students' academic achievement. Key factors such as trust, effective communication, emotional support, and responsiveness to individual student needs play a crucial role in forming supportive and effective relationships. Teachers who can build positive relationships can enhance students' intrinsic motivation and strengthen their engagement in the learning process. Practical implications of this research include the importance of professional development for teachers to strengthen their interpersonal skills. Schools also need to consider an active role in creating an environment that supports positive interactions between teachers and students, thereby enhancing overall student learning experiences. This study provides a deeper understanding of how teacher-student relationships can serve as a critical foundation in creating an inclusive learning environment and promoting students' holistic development. Future research could further explore specific strategies to enhance these relationships in various educational contexts.